ANALISA FAKTOR PENYEBAB RENDAHNYA KINERJA PERAWAT PELAKSANA DI RUMAH SAKIT KOTA MEDAN - Kristina L. Silalahi; Patimah Sari Siregar (Jurnal Keperawatan Priority, 2021)
Hospital is a health service with excellent and competitive service demands by its users. The function of the hospital was developed by the guidance of science and technology at its time. Performance appraisal is the most reliable tool for managers to control human resources and productivity and can be used effectively to direct employee behavior to produce nursing services based on high quality and quantity. The purpose of this study was to analyze the factors causing the low performance of nurses in Medan city hospital. This type of research is a quantitative study with a cross-sectional study design. This research was conducted at the Royal Prima Medan Hospital in July. The sample in this study were all nurses who served in the inpatient room. The sampling technique in this study using saturated sampling techniques totaling 159 nurses. Data collection using a questionnaire with the chi-square test. The results showed that the three-dimensional factors of nurse performance had a relationship with the performance of nurses, namely individual factors p = 0.000, psychological factors p = 0.006, and organization p = 0.002. This research concludes that the majority of nurses in the hospital still have low performance. The researcher's suggestion for the hospital is that the hospital pays more attention to the performance of the nurses who work in the inpatient room.